Formation of turbulent patterns near the onset of transition in plane Couette flow - Duguet, Y.; Schlatter, Philipp; Henningson, D. S. (Journal of Fluid Mechanics, 2010)
The formation of turbulent patterns in plane Couette flow is investigated near the onset of transition, using numerical simulation in a very large domain of size 800 h 2 h 356 h. Based on a maximum observation time of 20 000 inertial units, the threshold for the appearance of sustained turbulent motion is Rec = 324 1. For Rec < Re 380, turbulent-banded patterns form, irrespective of whether the initial perturbation is a noise or localized disturbance. Measurements of the turbulent fraction versus Re show evidence for a discontinuous phase transition scenario where turbulent spots play the role of the nuclei. Using a smaller computational box, the angle selection of the turbulent bands in the early stages of their development is shown to be related to the amplitude of the initial perturbation. Copyright © Cambridge University Press 2010.
CRIS-Team Scopus Importer:2023-03-21